From Green HRM to sustainability: A study of ground handling in java with employee performance as a key link - Faeni, Ratih Puspitaningtyas; Feani, Dewi Puspaningtyas; Pujiati, Heni; Cahaya, Yohannes Ferry (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to examine the direct and indirect relationship between Green HRM variables, as well as provide theoretical and practical contributions in the development of environmentally friendly HR management strategies in the ground handling company. Methodology/approach: Using a descriptive method with a purposive sampling technique. A total of 160 respondents from ground handling company were used as samples. Primary data is collected through questionnaires (g-form), and secondary data comes from various publication sources. The analysis used includes regression, correlation, percentage, and SEM. Results/findings: Green Recruitment, Green Training, and Green Performance Appraisal have a significant effect on Employee Performance through the mediation of Organizational Sustainability. Environmentally-oriented HR policies have been proven to improve organizational sustainability and employee performance. Conclusions: Green HRM practices have a direct and indirect effect on employee performance and organizational sustainability. The integration of eco-friendly principles in HR strategies is essential for long-term productivity and sustainability. Limitations: The study was limited to companies java province, the potential for questionnaire bias, the approach was only quantitative, and did not consider external factors such as organizational culture and leadership. Contribution: This research reinforces the importance of implementing GHRM in improving employee performance and organizational sustainability, as well as encouraging follow-up research with qualitative approaches and external factors.